Increased protein encapsulation in polymersomes with hydrophobic membrane anchoring peptides in a scalable process - Mertz, Michael; Castiglione, Kathrin (International Journal of Molecular Sciences, 2021)
Hollow vesicles made from a single or double layer of block-copolymer molecules, called polymersomes, represent an important technological platform for new developments in nano-medicine and nano-biotechnology. A central aspect in creating functional polymersomes is their combination with proteins, especially through encapsulation in the inner cavity of the vesicles. When producing polymersomes by techniques such as film rehydration, significant proportions of the proteins used are trapped in the vesicle lumen, resulting in high encapsulation efficiencies. However, because of the difficulty of scaling up, such methods are limited to laboratory experiments and are not suitable for industrial scale production. Recently, we developed a scalable polymersome production process in stirred-tank reactors, but the statistical encapsulation of proteins resulted in fairly low encapsulation efficiencies of around 0.5%. To increase encapsulation in this process, proteins were genetically fused with hydrophobic membrane anchoring peptides. This resulted in encapsulation efficiencies of up to 25.68%. Since proteins are deposited on the outside and inside of the polymer membrane in this process, two methods for the targeted removal of protein domains by proteolysis with tobacco etch virus protease and intein splicing were evaluated. This study demonstrates the proof-of-principle for production of protein-functionalized polymersomes in a scalable process.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Functionalization; Hydrophobic peptide; Polymer vesicle; Polymersome; Protein encapsulation